De novo transcriptome sequencing and analysis of Coccinella septempunctata L. in non-diapause, diapause and diapause-terminated states to identify diapause-associated genes. (December 2015) - Qi, Xiaoyang; Zhang, Lisheng; Han, Yanhua; Ren, Xiaoyun; Huang, Jian; Chen, Hongyin
Abstract Background The most common ladybird beetle, Coccinella septempunctata L., is an excellent predator of crop pests such as aphids and white flies, and it shows a wide range of adaptability, a large appetite and a high reproductive ability. Diapause research plays an important role in the artificial propagation and shelf-life extension of insect products. Although this lady beetle's regulatory, physiological and biochemical characteristics in the diapause period are well understood, the molecular mechanism of diapause remains unknown. Therefore, we collected female adults in three different states, i.e., non-diapause, diapause and diapause termination, for transcriptome sequencing. Results After transcriptome sequencing using the Illumina HiSeq 2500 platform with pretreatment, a total of 417.6 million clean reads from nine samples were filtered using the program FASTX (version 0.0). Additionally, 106, 262 contigs were assembled into 82, 820 unigenes with an average length of 921 bp and an N50 of 1, 241 bp. All of the unigenes were annotated through BLASTX alignment against the Nr or UniProt database, and 37, 872 unigenes were matched. We performed further analysis of these unigenes using the Clusters of Orthologous Groups of proteins (COG), Gene Ontology (GO), and the Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Through pairwise comparisons of the non-diapause (ND), diapause (D), and diapause-terminated (DT) groups, 3, 501 and 1, 427 differentially expressed genes (DEGs) were identified between D and ND and between DT and D, respectively. Moreover, 443 of the DEGs were specifically expressed during the diapause period (i.e., DEGs that were expressed at the highest or lowest levels during diapause compared with the other stages). GO function and KEGG pathway enrichment were performed on all DEGs and showed that RNA-directed DNA polymerase activity and fatty acid metabolism were significantly affected. Furthermore, eight specific expressed genes were selected for validation using qRT-PCR. Among these eight genes, seven genes were up-regulated, and one gene was down-regulated; the change trends of the eight genes were the same between the qRT-PCR and RNA-seq analysis results. Conclusions In this study, a new method for collecting and identifying diapause insects was described. We generated a vast quantity of transcriptome data fromC. septempunctata L., providing a resource for gene function research. The diapause-associated genes that we identified establish a foundation for future studies on the molecular mechanisms of diapause.